Unicompartmental and total knee arthroplasty in the treatment of knee osteoarthritis - Knifsund, Jani (fi=Turun yliopisto|en=University of Turku|, 2021)
Even though total knee arthroplasty has been a highly successful operation, as many as 20% of patients are somewhat dissatisfied with their prosthesis. In at least 25% of patients, the pattern of osteoarthritis is isolated medial, which could be treated with medial unicompartmental rather than total knee arthroplasty. Medial unicompartmental arthroplasty has been associated with a shorter hospital stay, faster recovery time, lower cost, subjective preference for a more normal-feeling knee, and reduced perioperative morbidity and mortality compared with total knee arthroplasty. However, its survival has been inferior to that of total knee arthroplasty in national registries. The primary objective of this study was to evaluate the influence of the preoperative degree of knee osteoarthritis on the risk of reoperation; to determine the short-term survivorship of cementless mobile-bearing unicompartmental arthroplasty and to compare that of cemented mobile-bearing unicompartmental arthroplasty and total knee arthroplasty; to evaluate the clinical effectiveness of medial unicompartmental knee arthroplasty versus total knee arthroplasty in a randomized, controlled, assessor-blind comparison. We found that in the preoperative weight-bearing radiographs, the degree of knee osteoarthritis should be severe, to diminish the revision rate. In the short term, use of a cementless unicompartmental device is associated with increased survivorship over the use of a cemented device and the functional outcome scores favored medial unicompartmental arthroplasty at 2 months and 1-year follow-up but the primary outcome were comparable for medial unicompartmental arthroplasty and total knee arthroplasty at 2 years. The present study supports the use of medial unicompartmental arthroplasty in patients with anteromedial arthritis. The revision rate can be reduced by following the original indications and using cementless mobile-bearing components. Medial unicompartmental arthroplasty provides a comparable outcome for medial unicompartmental arthroplasty and total knee arthroplasty at 2 years and faster postoperative recovery than total knee arthroplasty. However, the overall survivorship of mobile-bearing unicompartmental knee arthroplasty is inferior to that of cemented total knee arthroplasty and must be taken into consideration.

Osatekonivel ja kokotekonivel polven nivelrikon hoidossa Vaikka kokotekonivelleikkaus on erittäin hyvä hoitomuoto, niin jopa 20 % potilaista on leikkauksen jälkeen osittain tyytymättömiä lopputulokseen. Vähintään 25 %:lla potilaista polven nivelrikko on rajoittunut polven sisäreunalle ja osatekonivel soveltuu näiden potilaiden hoitoon. Osatekonivelen etuina kokotekonivelleikkaukseen verrattuna ovat muun muassa lyhyempi sairaalahoitoaika, nopeampi toipuminen toimenpiteestä, edullisempi hoidon hinta, sekä pienempi leikkauksen jälkeinen sairastuvuus ja kuolleisuus. Lisäksi leikattu polvi voi myös tuntua enemmän omalta polvelta. Siitä huolimatta sen uusintaleikkausriski on ollut merkittävästi korkeampi kaikissa kansallisissa tekonivelrekistereissä. Tämän tutkimuksen tavoitteena oli: 1) selvittää leikkausta edeltävän nivelrikon vaikeuden vaikutusta leikkauksen jälkeiseen uusintaleikkausriskiin. 2) Selvittää sementillisen ja sementittömän osatekonivelen uusintaleikkausriskiä lyhyellä aikavälillä verrattuna polven kokotekoniveleen. 3) Selvittää polven osatekonivelleikkauksen vaikuttavuutta verrattuna polven kokotekonivelleikkaukseen kontrolloidussa, kaksoissokkoutetussa vertailututkimuksessa. Tutkimuksen johtopäätöksenä voidaan todeta, että polven nivelrikon aste seisten otetussa kuormitusröntgenkuvauksessa tulee olla pitkälle edennyt, jotta uusintaleikkausmäärä vähenee. Polven sementittömän osatekonivelen pysyvyys oli viiden vuoden seurannassa parempi kuin sementillisen ja polven osatekonivelleikkauksesta toipuminen tapahtui nopeammin verrattuna kokotekonivelleikkaukseen. Tämän tutkimuksen perusteella polven osatekonivelen uusintaleikkausmääriä voidaan vähentää pitäytymällä alkuperäisissä indikaatioissa, välttämällä lievän nivelrikon hoitoa tekonivelleikkauksella ja käyttämällä sementitöntä osatekoniveltä. Polven osatekonivelleikkaus tuottaa potilaalle nopeamman toipumisen ja tulos kahden vuoden kohdalla on verrannollinen kokotekonivelleikkauksen tulokseen. Tämä tutkimus tukee polven osatekonivelen käyttöä polvinivelen sisäpuolen nivelrikon hoitona. On kuitenkin huomioitava, että polven osatekonivelen pysyvyys on sementöityä kokotekoniveltä huonompi.